2021
DOI: 10.1002/adma.202100770
|View full text |Cite
|
Sign up to set email alerts
|

40.1% Record Low‐Light Solar‐Cell Efficiency by Holistic Trap‐Passivation using Micrometer‐Thick Perovskite Film

Abstract: Perovskite solar cells exhibit not only high efficiency under full AM1.5 sunlight, but also have great potential for applications in low‐light environments, such as indoors, cloudy conditions, early morning, late evening, etc. Unfortunately, their performance still suffers from severe trap‐induced nonradiative recombination, particularly under low‐light conditions. Here, a holistic passivation strategy is developed to reduce traps both on the surface and in the bulk of micrometer‐thick perovskite film, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
128
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 48 publications
6
128
0
Order By: Relevance
“…Some groups have evaluated the manufacturing cost of perovskite modules with different geometries and have proposed related estimates of LCOE. 118,174,175 Han et al concluded that perovskite photovoltaic modules could be produced with simplified module geometry at an ultra-cost of $30–41 per square meter (excluding back-sealing glass, junction boxes, or wires). According to their assumptions, the LCOE value can be as low as 3.5–4.9 cents per kilowatt per hour, which is much lower than the cost of fossil fuel.…”
Section: Challenges and Opportunities Of Pipvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups have evaluated the manufacturing cost of perovskite modules with different geometries and have proposed related estimates of LCOE. 118,174,175 Han et al concluded that perovskite photovoltaic modules could be produced with simplified module geometry at an ultra-cost of $30–41 per square meter (excluding back-sealing glass, junction boxes, or wires). According to their assumptions, the LCOE value can be as low as 3.5–4.9 cents per kilowatt per hour, which is much lower than the cost of fossil fuel.…”
Section: Challenges and Opportunities Of Pipvsmentioning
confidence: 99%
“… 115 They believed that PSCs could play a role as a cost leader in the PV field if the key remaining issues can be resolved. 118 Furthermore, this estimated cost will be further reduced with large-area processes ( e.g. , roll-to-roll (R2R) and screen printing), low-cost transport layers, or electrode materials that are widely used in PIPV.…”
Section: Challenges and Opportunities Of Pipvsmentioning
confidence: 99%
“…The black phases of CsPbI 3 have aroused widespread attention in the photovoltaics community due to its exceptional photovoltaic properties such as higher efficiency, excellent chemical and thermal stability, which act as a potential candidate for solar cells. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] In recent years, the power conversion efficiency (PCE) of CsPbI 3 perovskite solar cells (PSCs) climbed rapidly from 2.9% first reported by Snaith and co‐workers to 20.8% by Liu and co‐workers, and the efficiency gap between the CsPbI 3 and organic–inorganic hybrid PSCs is further reduced. [ 8 , 9 , 10 , 11 , 12 ] Furthermore, CsPbI 3 has a suitable bandgap (≈1.70 eV) and can be used as the top cell of tandem photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells (PSCs), as one of the most promising photovoltaic technologies in the past decade, have gained considerable attention worldwide. [1][2][3][4][5] Despite the record power conversion efficiency (PCE) of 25.5 % announced in 2021, [6] the widely adopted metal halide organic-inorganic hybrid perovskites as active materials contain organic components (e.g. methylammonium (MA)), whose high volatility would threaten the long-term operational stability of devices.…”
mentioning
confidence: 99%